Are EU firms climate-ready? Micro evidence from EIBIS - Fotios Kalantzis; Sofia Dominguez (European Investment Bank (EIB), 2022)
This study uses unique firm-level data from EIBIS to identify EU firms' climate strategies and their associated factors. To do so, we initially run a clustering analysis that results in five distinct clusters in line with the literature and then investigate the role of various firms' characteristics in their adoption based on a multi-logit regression. Our findings show that almost half of the EU firms adopt either "wait-and-see" strategies or plan to invest in tackling climate change risks. More climate-friendly strategies appear to be positively associated with the awareness of climate-related risks, especially with firms that see the transition to a lowcarbon future as an opportunity. Similarly, those strategies are followed by large firms that are innovative, face fewer credit constraints and operate in an environment where there is a strong push for climate actions from various stakeholders. These findings are valuable as they can guide policymakers on supporting firms' transformation to play their part, as an integral part of our society, in the road to a clean, affordable, and secure energy future.
Keywords: 330; EIBIS; climate strategies; climate change risks; perception analysis; clustering analysis